Davey Whittaker
07/25/2023 · Junior High School

rcicio 2: Resuelvan las siguientes ecuaciones a. \( -4 x+2 x-7=-x+14+2 x-54:(-9) \) b. \( 4 \cdot(x-5)+16=16+5 \cdot(x-2) \) c. \( -4+4 \cdot(8-3 x)=-2 \cdot(2+3 x)+8 \) d. \( x^{3}-3=-30 \)

UpStudy ThothAI Solution

Tutor-Verified Answer

Step-by-step Solution

Solve the equation \( -4x+2x-7=-x+14+2x-54 \). Solve the equation by following steps: - step0: Solve for \(x\): \(-4x+2x-7=-x+14+2x-54\) - step1: Cancel equal terms: \(-4x-7=-x+14-54\) - step2: Subtract the numbers: \(-4x-7=-x-40\) - step3: Move the variable to the left side: \(-4x-7+x=-40\) - step4: Add the terms: \(-3x-7=-40\) - step5: Move the constant to the right side: \(-3x=-40+7\) - step6: Add the numbers: \(-3x=-33\) - step7: Change the signs: \(3x=33\) - step8: Divide both sides: \(\frac{3x}{3}=\frac{33}{3}\) - step9: Divide the numbers: \(x=11\) Solve the equation \( 4 \cdot(x-5)+16=16+5 \cdot(x-2) \). Solve the equation by following steps: - step0: Solve for \(x\): \(4\left(x-5\right)+16=16+5\left(x-2\right)\) - step1: Cancel equal terms: \(4\left(x-5\right)=5\left(x-2\right)\) - step2: Calculate: \(4x-20=5\left(x-2\right)\) - step3: Calculate: \(4x-20=5x-10\) - step4: Move the expression to the left side: \(4x-20-\left(5x-10\right)=0\) - step5: Calculate: \(-x-10=0\) - step6: Move the constant to the right side: \(-x=0+10\) - step7: Remove 0: \(-x=10\) - step8: Change the signs: \(x=-10\) Solve the equation \( -4+4 \cdot(8-3x)=-2 \cdot(2+3x)+8 \). Solve the equation by following steps: - step0: Solve for \(x\): \(-4+4\left(8-3x\right)=-2\left(2+3x\right)+8\) - step1: Move the expression to the left side: \(-4+4\left(8-3x\right)-\left(-2\left(2+3x\right)+8\right)=0\) - step2: Calculate: \(6x+4\left(8-3x\right)-8=0\) - step3: Calculate: \(-6x+24=0\) - step4: Move the constant to the right side: \(-6x=0-24\) - step5: Remove 0: \(-6x=-24\) - step6: Change the signs: \(6x=24\) - step7: Divide both sides: \(\frac{6x}{6}=\frac{24}{6}\) - step8: Divide the numbers: \(x=4\) Solve the equation \( x^{3}-3=-30 \). Solve the equation by following steps: - step0: Solve for \(x\): \(x^{3}-3=-30\) - step1: Move the constant to the right side: \(x^{3}=-30+3\) - step2: Add the numbers: \(x^{3}=-27\) - step3: Simplify the equation: \(\sqrt[3]{x^{3}}=\sqrt[3]{-27}\) - step4: Calculate: \(x=\sqrt[3]{-27}\) - step5: Simplify the root: \(x=-3\) a. La solución de la ecuación \( -4x+2x-7=-x+14+2x-54 \) es \( x=11 \). b. La solución de la ecuación \( 4 \cdot(x-5)+16=16+5 \cdot(x-2) \) es \( x=-10 \). c. La solución de la ecuación \( -4+4 \cdot(8-3x)=-2 \cdot(2+3x)+8 \) es \( x=4 \). d. La solución de la ecuación \( x^{3}-3=-30 \) es \( x=-3 \).

Quick Answer

a. \( x=11 \) b. \( x=-10 \) c. \( x=4 \) d. \( x=-3 \)
Answered by UpStudy AI and reviewed by a Professional Tutor
UpStudy ThothAI
Self-Developed and Ever-Improving
Thoth AI product is constantly being upgraded and optimized.
Covers All Major Subjects
Capable of handling homework in math, chemistry, biology, physics, and more.
Instant and Accurate
Provides immediate and precise solutions and guidance.
Try Now
Ask Tutors
Ask AI
10x
Fastest way to Get Answers & Solutions
By text

Enter your question here…

By image
Re-Upload
Uploaded Files
xxxx.png0%
Submit
📸 STUDY CAN BE A REAL STRUGGLE
Why Not UpStudy It?
Select your plan below
Premium

You can enjoy

  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to answer and
    solution
Basic
  • Limited Solutions